Return
Entire thread
Please help with this functional differential equation.
7
Name:
Anonymous
2021-04-17 17:54
Quoted by:
>>8,9
y = Ax^3
So you're looking for
6Ax = A(Ax^3)^3
6x = (Ax^3)^3
6x = (Ax^3)(Ax^3)(Ax^3)
(6/A)x = x^9
6/A = x^8
A = 6/(x^8)
Plug it in the original equation
y = 6x^3 / x^8
y = 6 / x^5
Return
Entire thread
Name:
Sage
Leave this field blank:

So you're looking for

6Ax = A(Ax^3)^3

6x = (Ax^3)^3

6x = (Ax^3)(Ax^3)(Ax^3)

(6/A)x = x^9

6/A = x^8

A = 6/(x^8)

Plug it in the original equation

y = 6x^3 / x^8

y = 6 / x^5